A 61-year-old Filipino man with lichen planus concomitant with cicatricial alopecia, mimicking discoid lupus erythematosus - Harris, Lie Michelle E.; Carpio, Benedicto dL; Regalado-Morales, Eileen; Guzman, Amelita Tanglao-De; Lapitan-Torres, Armelia (Journal of General - Procedural Dermatology and Venereology Indonesia, 2023)
Background: Lichen planus (LP) is an idiopathic inflammatory disease affecting the skin, mucous membranes, hair, and nails. Even though rare, LP may also present as cicatricial alopecia or a condition referred to as lichen planopilaris (LPP). On the other hand, lupus erythematosus (LE) is an autoimmune disorder with a possibility of systemic involvement. Classical discoid lupus erythematosus (DLE) is the most common form of LE and has a hallmark of scarring alopecia. Case Illustration: A 61-year-old Filipino man presented with a 7-month history of persistent multiple erythematous hairless scarring plaques on the scalp with multiple erythematous–violaceous to hyperpigmented atrophic plaques on the face and distal upper extremities. Discussion: The remarkable atrophic scarring alopecia on the scalp, along with the atrophic coin-shaped plaques on the face and extensor aspects of both forearms on this patient, brought DLE as the initial clinical impression. Besides cicatricial alopecia being a prevalent feature of DLE, the noticeable scarring alopecia on the scalp with the concomitant appearance of multiple atrophic skin lesions on sun-exposed areas supported this reasoning. Nevertheless, the skin punch biopsy of this patient showed numerous histopathological features of LP. Conclusion: LP can present with several morphological cutaneous presentations, including atrophic LP, which may mimic cutaneous DLE. Even though LP is a non-scarring disease, a follicular variant of LP, LPP has a distinct clinical and histologic entity with associated scarring alopecia. The presence of atrophic cutaneous LP concomitant with scalp LPP may mimic DLE clinically.